Regulation of B-cell development and function by microRNAs - de Yébenes, Virginia G; Bartolomé-Izquierdo, Nahikari; Ramiro, Almudena R. (Immunological reviews, 2013)
Summary MicroRNAs (miRNAs) have emerged as a new class of gene expression regulators whose functions influence a myriad of biological processes, from developmental decisions through immune responses and numerous pathologies, including cancer and autoimmunity. miRNAs are small RNA molecules that drive post‐transcriptional negative regulation of gene expression by promoting the degradation or translational block of their target mRNAs. Here, we review some of the data relating to the role of miRNAs in the regulation of the B‐cell lineage, with a special focus on results obtained in vivo. We start by giving a general overview of miRNA activity, including the issue of target specificity and the experimental approaches more widely used to analyze the function of these molecules. We then go on to discuss the function of miRNAs during B‐cell differentiation in the bone marrow and in the periphery as well as during the humoral immune response. Finally, we describe a few examples of the contribution of miRNAs, both as oncogenes and tumor suppressors, to the development of B‐cell neoplasias.